2008
DOI: 10.1007/s11595-007-5632-y
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and microstructure of Ta2O5 thin films prepared by ion assisted electron beam evaporation

Abstract: An effective method for determining the refractive index of weak absorption transparent thin films was presented, which is also applicable to other weak absorption dielectric thin films. The as-deposited Ta 2 O 5 thin films prepared by ion assisted electron beam evaporation showed a maxima transmittance as high as 93% which was close to that of the bare substrate, and exhibited a blue shift when the substrate temperature increased from room temperature to 250 ℃. The refractive index seemed to be immune to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, in the case of the Ta 2 O 5 -EB thin films, the R a extracted from AFM images was 0.48 nm, compared with 0.99 nm determined by XRR. It has already been reported that XRR experiments tend to overestimate the values of surface roughness [40,41]. Additionally, the inclusion of interfacial layers in the XRR fitting model would probably improve the certainty.…”
Section: Xrrmentioning
confidence: 99%
“…For example, in the case of the Ta 2 O 5 -EB thin films, the R a extracted from AFM images was 0.48 nm, compared with 0.99 nm determined by XRR. It has already been reported that XRR experiments tend to overestimate the values of surface roughness [40,41]. Additionally, the inclusion of interfacial layers in the XRR fitting model would probably improve the certainty.…”
Section: Xrrmentioning
confidence: 99%
“…1) using the method reported in [5]. The results in Table 1 show that the refractive indices of the films with added DMF, especially which with 10% DMF, are lower than those of dense SiO 2 films without DMF.…”
Section: Effects Of Dmf Concentration On the Optical Property Of Sio2mentioning
confidence: 97%
“…Because of its properties Ta 2 O 5 is also employed in integrated sensors for hydrogen ion sensing membranes or protein detection, making it sought after in the field of biological and biochemical sensors [3]. Tantalum pentoxide, due to its high refractive index and very low absorption coefficient [4], is also suitable for the fabrication of thin films for the purposes of antireflective coatings for solar cells or CCD devices, and for protection of material surfaces against corrosion because of its high chemical stability [5]. Preparation of Ta 2 O 5 has been a challenging issue, but there are a number * E-mail: kasparp@feec.vutbr.cz of possible methods to create thin Ta 2 O 5 layers, with varying degree of success and specific properties of the prepared layer.…”
Section: Introductionmentioning
confidence: 99%